Nuevas citas de macrófitos acuáticos de las zonas húmedas de la provincia de Málaga - Nieto Caldera, José María; Conde-Alvarez, Rafael Miguel; Arrebola Bautista, María Ángeles; Flores-Moya, Antonio (Acta Botanica Malacitana, 1997)
.